Estimativa dos níveis de bioaerossóis e compostos orgânicos voláteis fúngicos em ambientes ocupacionais no município de Fortaleza - Ceará - Pantoja, Lydia Dayanne Maia (2016)
The search for more accurate methods of characterization of fungal composition in the air is required. It is known that when fungi develop within the structure of a building or ventilation filters, clearly there is a reasonable amount of \"hidden contamination\" can not be detected only through visual inspection. As well, the fact is that the fungi when they start to develop emit into the atmosphere Organic Compounds Fungal Volatile (COVFs), arising from the metabolic pathways or from degradation materials due to the release of enzymes produced by them. In the meantime, the goal of this thesis was to estimate the indoor air quality via bioaerosols and COVFs order improvements in monitoring and control of occupational environments in Fortaleza, Ceará. Therefore, there was the analysis of the researched environments (tertiary hospital, shopping center and public library) and application questionnaire to users in order to analyze the worker\'s understanding of the air quality. Then there was the preparation and validation of a protocol for determining COVFs. For the analysis of COVFs was used gas chromatography coupled to mass spectrometry is performed on Analysis Laboratory Trace - UFC. As for fungal samples were sent the Microbiology Laboratory - UECE, in order to identify through macro analysis and micromorphological and biochemical tests. 144 samples were analyzed front of COVFs, with nine compounds were detected in at least one of the sectors considered and only 3-octanone was not observed. In the quantitative analysis, with the highest COVFs concentrations (in g / m3) were 2-methyl-1-propanol, 3-methyl-1-butanol and 2-heptanone. At the regard to fungal findings, 72 samples were analyzed, being observed a high number of colony forming units per cubic meter (UFC.m-3) in all environments, in particular the general collection (3,497 UFC.m-3), followed by the center covered parking commercial (3245 UFC.m-3). While regarding the fungi spectrum composition airborne the three environments, it is formed predominantly by filamentous hyaline, especially the genus Aspergillus sp., and yeasts such as Candida species tropicalis. We evaluated the relationship between COVFs and fungal strains, and found the presence Six similarity groups such as 2-methyl-1-propanol which had a distribution space similar to fungi Acremonium sp., Aspergillus niger, Candida tropicalis and Penicillium sp. Also, we analyzed the distribution of the quantity of sample and COVFs Fungal by seasons, there was a significant difference between fungal samples and seasonality. The data presented mapped existence in the presence of COVFs working environments analyzed, characterizing the need for control of these compounds in ambient air indoor. Through research is expected to provide improved the current monitoring in the absence of national legislation on the COVFs, aiming in the future assist decision making managers in relation to occupational hazards, prompting further discussion in the academic and legislative environment and ultimately contribute to the systematic study of Aerobiology in the country.